Perbandingan Kuat Tekan Beton dengan Subtitusi Fly Ash Ditinjau dari Air Laut dan Air Tawar pada Proses Curing - Dewi Pertiwi; Dewi Kusumaningrum; Yanisfa Septiarsilia; Jaka Propika; Eka Susanti; Heri Istiono (Institut Teknologi Adhi Tama Surabaya, 2025)
Curing plays a vital role in concrete production, as proper treatment is essential before conducting a compressive strength test to ensure optimal results. Concrete cured in seawater often exhibits different strength characteristics due to the salt content. This study examines the effects of curing with both seawater and freshwater on concrete containing fly ash. The research aims to compare the compressive strength of concrete with fly ash substitution under two different curing conditions. Using an experimental approach, the study incorporated 40% fly ash and 1% polycarboxylate admixture into the concrete mix to target a high compressive strength of K-500. Results indicate that concrete with fly ash cured in seawater achieved an average compressive strength of 807.40 kg/cm² at 28 days, while concrete cured in freshwater reached only 667.94 kg/cm².